2019
DOI: 10.3168/jds.2018-15538
|View full text |Cite
|
Sign up to set email alerts
|

Activation of liver X receptor promotes fatty acid synthesis in goat mammary epithelial cells via modulation of SREBP1 expression

Abstract: In bovine mammary tissue and cells, liver X receptor (LXR) regulates lipid synthesis mainly via transactivation of the transcription factor sterol regulatory element binding protein 1 (SREBP1). In the present work, we investigated the role of LXR in controlling lipid synthesis via transactivation of SREBP1 in goat primary mammary cells (GMEC). The GMEC were treated with a synthetic agonist of LXR, T0901317, and transactivation and transcription of SREBP1, expression of lipogenic genes, and fatty acid profiling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 69 publications
(113 reference statements)
1
13
0
Order By: Relevance
“…LXR also directly stimulates the transcription of specific lipogenic genes, including acetyl-CoA carboxylase α ( ACACA ) in chick embryos and fatty acid synthase ( FASN ) in human cells. 90 Diosgenin (10, 25, and 50 µM) significantly inhibited the accumulation of TG and the increase of SREBP-1c mRNA in HepG2 cells induced by high glucose levels. In addition, compared with the model group, diosgenin (0.5% or 1% w/w) treated rats fed with a HFD also exhibited significantly suppressed LXRα levels.…”
Section: The Pharmacological Mechanism Underlying the Use Of Diosgenin For Treatment Of Hyperlipidemiamentioning
confidence: 93%
“…LXR also directly stimulates the transcription of specific lipogenic genes, including acetyl-CoA carboxylase α ( ACACA ) in chick embryos and fatty acid synthase ( FASN ) in human cells. 90 Diosgenin (10, 25, and 50 µM) significantly inhibited the accumulation of TG and the increase of SREBP-1c mRNA in HepG2 cells induced by high glucose levels. In addition, compared with the model group, diosgenin (0.5% or 1% w/w) treated rats fed with a HFD also exhibited significantly suppressed LXRα levels.…”
Section: The Pharmacological Mechanism Underlying the Use Of Diosgenin For Treatment Of Hyperlipidemiamentioning
confidence: 93%
“…Moreover, since adult cardiomyocytes use fatty acids for 70% of the ATP used for contractility (72), the long-term suppression of Fasn, Scd1, and other fatty acid synthesis genes may affect the functionality of the remaining cardiomyocytes after they have stopped proliferating and further contribute to the diastolic heart failure. Agonists for nuclear hormone receptors that work with SREBF1 to induce lipogenesis, such as liver X receptor (LXR) and PPARG, are currently available (73)(74)(75)(76)(77). Future studies will be needed to determine if these compounds can be used to protect or restore the postnatal proliferation and survival of atrial cardiomyocytes in mice exposed to hyperoxia and potentially lead to novel therapies to prevent diastolic heart failure in individuals who were born preterm.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that t10c12-CLA, PPARG and PPARD exhibit positive regulation of both CD36 (35, 87, 106) and ACSL1 (34,36,63), however, Shi et al (61) challenge the above view that t10c12-CLA A positively regulates CD36 and ACSL1, which may be related to factors such as the species, mode and amount of additives, the exact mechanism of action needs to be further verified by more in-depth experimental studies as well as large-scale populations. As previously described, 14-3-3γ, LXR, SREBP1 and CIDEC have positive regulatory roles in the de novo synthesis of milk fat, which perform similar functions during LCFA uptake (21,29,36,69). The SLC27 family (SLC27A1 to SLC27A6) is considered to be bifunctional proteins with LCFA transport and acyl-CoA synthetase activity.…”
Section: Lcfa Uptake and Activationmentioning
confidence: 91%
“…In addition, FASN, ATGL, CIDEA and LXR positively regulated the expression of XDH and Btn1a1 in ruminants (29,45,86,113).…”
Section: Regulation Of Xdh and Btn1a1mentioning
confidence: 91%